Pedagogical experiences of pre-service teachers facing in-person EFL classes - Parra Suárez, Camila Andrea; Ruíz Euce, Laura Daniela; Suárez Vega, Karen Andrea (Corporación Universitaria Minuto de Dios – UNIMINUTO, 2024)
This monograph is a qualitative Case Study that aims to explore the pedagogical experiences of pre-service teachers when faced with face-to-face teaching of English as a foreign language. It also aims to demonstrate the effectiveness of pedagogical tools such as Communicative Language Teaching and Total Physical Response in solving frequent classroom problems. The data collection was conducted through semi-structured qualitative interviews, a perception questionnaire and observations where its results focused on the problems when applying the theory in real aspects of the profession, assessing what was learned in the degree helped the pre-service teachers to develop as competent educators in real classroom aspects. Additionally, this study was conducted to identify and propose strategies based on the experiences of 10 pre-service teachers, whose opinions were analyzed using coding techniques to identify patterns and emerging themes. Moreover, the results will help shed light on what difficulties pre-service teachers face in practice, describing and analyzing them in order to contribute with tips and strategies oriented to students in the first semesters of the career, underlining that Communicative Language Teaching and Total Physical Response are essential for the resolution of difficulties in the classroom. In conclusion, the educational training and strategies of Communicative Language Teaching and Total Physical Response will be useful for beginning teachers if they are applied when facing significant challenges, considering the practical and realistic contexts where pre-service teachers face significant challenges when applying the theory in their classrooms.

La presente monografía es un estudio de caso cualitativo cuyo objetivo es explorar las experiencias pedagógicas de los profesores en formación cuando se enfrentan a la enseñanza presencial del inglés como lengua extranjera. También, se pretende demostrar la eficacia de herramientas pedagógicas como Communicative Language Teaching y Total Physical Response para resolver problemas frecuentes en el aula. La recolección de datos se realizó a través de entrevistas cualitativas semiestructuradas, un cuestionario de percepción y observaciones donde sus resultados se centraron en los problemas a la hora de aplicar la teoría en aspectos reales de la profesión, valorando si lo aprendido en la licenciatura ayudaba a los profesores en formación a desarrollarse como educadores. Adicionalmente, este estudio se llevó a cabo para identificar y proponer estrategias basadas en las experiencias de 10 profesores en formación, cuyas opiniones se analizaron mediante técnicas de codificación para identificar patrones y temas emergentes. Por otra parte, los resultados ayudarán a dar luz sobre cuáles son las dificultades a las que se enfrentan los profesores en formación en práctica, describiéndolas y analizándolas para contribuir con tips y estrategias orientadas a los estudiantes de primeros semestres de la carrera, subrayando que Communicative Language Teaching y Total Physical Response son esenciales para la resolución de dificultades en el aula de clase. En conclusión, la formación educativa y las estrategias como Communicative Language Teaching y Total Physical Response serán útiles para los profesores principiantes si se aplican al enfrentarse a retos significativos, teniendo en cuenta los contextos prácticos
To evaluate the effectiveness of Total Physical Response (TPR) and Communicative Language Teaching (CLT) based on the experiences of pre-service teachers from the ninth and tenth semesters of the bachelor's degree in foreign Languages at UNIMINUTO after their teaching practicum with young and adult students in face-to-face classes.
Keywords: apprenticeship; classroom techniques; skills development; teaching; pre-service teachers; aprendizaje; desarrollo de competencias inglés; Ingles - Enseñanza; Lenguas Germanicas; Educación